DEPENDENCE OF MORTALITY FROM CARDIOVASCULAR SYSTEM DISEASES ON METEOROLOGIC FACTORS AMONG POPULATION OF BAKU AND GUBA - V. A. Azizov; E. M. Hatamzade; A. S. Rahimova; A. K. Alekperova; T. A. Sadigova; A. Y. Mamedzade (Евразийский Кардиологический Журнал, 2018)
The article presents the results of study dependence of mortality from cardiovascular system diseases on meteorologic factors among population of Baku and Guba. Air temperature and rainfall have been taken as the main meteorological indicator for months. Increased risk of death from cardiovascular diseases in both cities was observed more in the spring-winter months than in the summer, which was associated with a high amount of precipitation at this time of the year and with a lower temperature.